2003
DOI: 10.1177/0146167202238377
|View full text |Cite
|
Sign up to set email alerts
|

White Guilt and Racial Compensation: The Benefits and Limits of Self-Focus

Abstract: In two studies, the authors investigated guilt as a response to group-based advantage. Consistent with its conceptualization as a self-focused emotion, White guilt was based in self-focused beliefs in racial inequality. Thus, guilt was associated with belief in White privilege (Study 1) and resulted from seeing European Americans as perpetrators of racial discrimination (Study 2). Just as personal guilt is associated with efforts at restitution, White guilt was predictive of support for affirmative action prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
478
3
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(536 citation statements)
references
References 28 publications
(75 reference statements)
41
478
3
14
Order By: Relevance
“…One of the most common emotions perpetrators battle during the discrimination process is guilt, a mechanism that motivates people to alter their actions in such a way that discourages deviance and promotes socially acceptable behavior (Amodio, Devine, & Harmon-Jones, 2007). Research has suggested guilt may be an effective means through which discrimination can be reduced (Iyer, Leach, & Crosby, 2003). To demonstrate this point, Monteith, Voils, and Ashburn-Nardo (2001) conducted a study in which participants were made aware of their implicit biases.…”
Section: Perpetrator Experience Of Subtle Discriminationmentioning
confidence: 99%
“…One of the most common emotions perpetrators battle during the discrimination process is guilt, a mechanism that motivates people to alter their actions in such a way that discourages deviance and promotes socially acceptable behavior (Amodio, Devine, & Harmon-Jones, 2007). Research has suggested guilt may be an effective means through which discrimination can be reduced (Iyer, Leach, & Crosby, 2003). To demonstrate this point, Monteith, Voils, and Ashburn-Nardo (2001) conducted a study in which participants were made aware of their implicit biases.…”
Section: Perpetrator Experience Of Subtle Discriminationmentioning
confidence: 99%
“…An argument that frequently surfaces in discussions on the desirability of a national apology for historical harmdoings is that those actions were committed by other members of the group-people that no longer are alive today (McGarty et al, 2005). Efforts toward restitution can stem from feelings of collective guilt (Iyer, Leach, & Crosby, 2003), but for feelings of collective guilt to arise and contribute to a group apology one needs to have a sense of identity that includes the perpetrators, as opposed to one from which they are excluded as a ''past generation '' (McGarty et al, 2005). As demonstrated by the results from Study 3 in the present research, an apology offered by the group was also perceived by outsiders as reflecting a higher level of inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…(örn., Doosje, Branscombe, Spears ve Manstead, 1998;Wohl ve Branscombe, 2008) veya "devam eden gruplar arası eşitsizliklerde iç grubun ayrıcalıklı statüsü nedeniyle kişiler grupları adına suçluluk duyar mı?" (örn., Iyer, Leach ve Crosby, 2003) gibi sorular ele alınmıştır. Bu soruların yanı sıra böylesi bir kolektif duygunun ortaya çıkmasını kolaylaştıran ya da engelleyen koşulların neler olduğu (örn., Jelic, Biruski ve Adjukovic, 2013) ve kolektif suçluluk hissetmemek için grup üyelerinin ne tür kaçınma yolları kullanabilecekleri (örn., Rothschild, Landau, Molina, Branscombe ve Sullivan, 2013) konuları incelenmiştir.…”
Section: öZunclassified